Endocannabinoid levels in newborns in relation to the mode of delivery - Jokisch, Viktoria; Kroll, Richard; Schaffelder, Regine; Schaible, Thomas (American journal of perinatology, 2015)
Objective: This study aims to examine the endocannabinoid levels in newborns in relation to the mode of delivery. Study Design: In this study, the concentrations of the endocannabinoids anandamide (AEA), 2-arachidonylglycerol (2-AG), palmitoylethanolamine (PEA), and the metabolite arachidonic acid (AA) in umbilical cord vein blood of 49 newborns was determined by quantitative mass spectrometry using liquid chromatography multiple reaction monitoring. The newborns were divided by their mode of delivery. Only healthy newborns born after 34 0/7 gestational weeks without birth complications were included. Results: The concentration of AEA, PEA, and AA was significantly higher in vaginal delivered newborns (n = 25) in comparison to newborns born by cesarean delivery (n = 24). 2-AG exhibited no significant differences between the groups. Conclusion: The exposure of the newborn to high endocannabinoid concentrations is a physiological process during vaginal delivery. The endocannabinoids AEA, PEA, and their metabolite AA seem to be part of an endocrine system during labor and birth supporting the fetal transition.